HUBUNGAN TINGKAT PENDIDIKAN, PENGETAHUAN DAN PEMBERDAYAAN MASYARAKAT DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) WARGA DI RUSUN HARUM JAKARTA SELATAN TAHUN 2016 - Agus Riyanto; Arni Widyastuti (CV. Multi Kreasi Media, 2023)
The study aims to determine the relationship of clean and healthy living behaviors (PHBS) in order households with level of education, level of knowledge, sanitation and community empowerment in Rusun Harum Tebet 2016. This research was a cross sectional descriptive. The study population was a family who settled in Rusun Harum was 320 families. Samples taken as many as 120 households using simple random sampling proportional method. Data analysis using Chi Square analysis. The results showed that the relationship PHBS with the level of education, level of knowledge, sanitation and community empowerment (extension of PHBS), show variable Empowering communities (extension of PHBS) have significance with PHBS variable (p value = 0.006).